Locus-coeruleus norepinephrine system function in a developmental animal model of schizophrenia: the socially isolated rat - Atmore, Katherine H (Department of Psychiatry and Mental Health, 2017)
Introduction: Schizophrenia is a chronic, debilitating mental disorder characterised by positive, negative and cognitive symptoms. Current treatment regimens fail to adequately address the cognitive and negative symptoms of the disorder. Social isolation rearing (SIR) is a well-established developmental adversity paradigm which is used as an animal model of schizophrenia and usually studied in male rats. Previous SIR studies have found attentional abnormalities in isolated rats in behavioural tests which correspond to the results of studies investigating the cognitive symptoms of schizophrenia in patient trials. Isolated rats also display abnormal social responses which may be of relevance to the negative symptoms of schizophrenia. The primary aim of this study was to build on existing SIR literature by performing behavioural tests in socially isolated rats to address attentional function. Neurochemical investigations were performed on projections of the locus coeruleus norepinephrine system, known to be involved in attentional function, as research on this system is surprisingly sparse. The secondary aim of the study was to address the negative symptoms of schizophrenia using ultrasonic vocalisation recording to investigate the calling behaviour of isolated rats in response to a novel context. The study included both male and female rats so that sex differences could be studied in the context of social isolation. Methodology: Sprague-Dawley rats were weaned at postnatal day (p) 21 and randomly allocated to one of four housing groups; female socialised (n=50), female isolated (n=50), male socialised (n=38) and male isolated (n=38). Socialised animals were housed 4 per cage (single sex) and isolated animals were housed alone. Animals were weighed and cages cleaned weekly as part of a minimal handling protocol required for SIR. After 8 weeks in their housing conditions (p78-82) rats underwent one of two behavioural paradigms: three phase novel object recognition or ultrasonic vocalisation recordings. Between p90-94 animals were rapidly decapitated and the hippocampus and prefrontal cortex were dissected out for use in one of two neurochemical analyses. For in-vitro superfusion experiments the tissue was used immediately to quantify functional release of radioactively-labelled norepinephrine when stimulated with glutamate under varying conditions. Enzyme linked immunosorbent assays (ELISA) and bicinchoninic acid (BCA) protein assays was performed to quantify norepinephrine and glutamate concentrations expressed in relation to the wet weight of the tissue and amount of protein in the tissue. Results: Behavioural and neurochemical changes were induced by the SIR model. Isolated animals were found to respond to novel objects abnormally compared to control animals. During initial exposure to a novel environment in the first phase of the novel object recognition test isolated animals demonstrated hypoactivity. An overall reduction in the fractional release of norepinephrine when stimulated with combinations of glutamate and gamma-aminobutyric acid (GABA) was demonstrated in the hippocampus of isolated rats. Sex differences were evident in a number of experiments. Female rats were found to be hyperactive in the three phases of the novel object recognition test compared to males and also had elevated hippocampal norepinephrine activity as well as an increased concentration of norepinephrine in this area. Male rats on the other hand had an elevated prefrontal cortex norepinephrine activity and concentration. Conclusion: The SIR paradigm is able to induce behavioural and neurochemical changes in both female and male rats. The results of this study reinforce the usefulness of SIR as a model for schizophrenia as the way in which isolated animals responded to novel objects was different to their socialised counterparts. This difference implies an abnormal attentional response which corresponds to the cognitive symptoms described in schizophrenia. Furthermore, the neurochemical experiments performed in this study are the first of their kind and provide preliminary evidence for the GABAergic mechanisms underlying attentional abnormalities associated with SIR. The prevalence of sex differences throughout testing also provides strong evidence for the inclusion of both sexes in future studies to avoid the omission of potentially important findings. Future studies to refine and build on neurochemical analyses in developmental models of schizophrenia, such as SIR will potentially provide a mechanistic understanding of cognitive dysfunction as well as useful translational information for treating the human disorder.